Atypical Familial Amyotrophic Lateral Sclerosis with Slowly Progressing Lower Extremities-predominant Late-onset Muscular Weakness and Atrophy - Togawa, Jumpei (Intern Med, 2019)
OBJECTIVE: Amyotrophic lateral sclerosis (ALS) is an adult-onset neurodegenerative disease characterized by the progressive loss of the upper and lower motor neurons that progresses to paralysis of almost all skeletal muscles of the extremities, bulbar, and respiratory system. Although most ALS cases are sporadic, about 10% are dominantly inherited. We herein report an atypical phenotype of familial ALS (fALS). To elucidate the phenotype-genotype correlation of this atypical phenotype of fALS, clinical and genetic investigations were performed. METHODS AND PATIENTS: Five sibling patients (three men, two women) from a Japanese family and one healthy sibling (a woman) were clinically interviewed and examined. Genetic analyses, including genome-wide linkage analyses and whole-exome sequencing, were performed using genomic DNA extracted from the peripheral blood samples of these siblings. RESULTS: The clinical features of fALS are characterized by slow progression (mean duration of the disease±standard deviation [SD]: 19.6±3.9 years) and lower extremities-predominant late-onset muscular weakness (mean onset of muscular weakness±SD: 52.8±2.6 years). Genetic analyses revealed novel heterozygous missense mutations of c.2668C>T, p.R890C in the PLEC gene and c.421G>C, p.V141L in the ST3GAL6 gene in all affected siblings. CONCLUSION: A new atypical fALS family with a benign clinical course is herein reported. We identified two candidate gene mutations of PLEC and ST3GAL6 linked to this phenotype.